Are the Benefits of Group Buying Limited to Monetary Value? A Study on the Ultimate Value of Online Group-Buying - Lin, Yu-Ling; Lin, Hong-Wen; Chu, Li-Chen (Asian Journal of Empirical Research, 2014)
The global prevalence of the Internet has effectively overcome the intangible limits of physical distance while elevating consumers’ inclination to engage in online shopping. Online group buying is now extremely popular during the bleak economic times. Therefore, the purpose of this paper is to identify the goal of customer in online group-buying. This study uses the theory of Mean-end chain as basis, applying the “Soft-laddering” of “Laddering” to understand the perceived value of online group-buying through depth interviews. Among the nine attribute variables, quantity-based pricing ranked first in terms of occurrence, followed by convenience and word-of-mouth marketing. Out of the eight consequence variables, cost-saving and opinion exchange ranked first, followed by effort and time saving and risk aversion. Finally, fun and enjoyment of life topped the nine value variables, followed by security and self-fulfillment. After classifying by content analysis, we draw the Hierarchical value map (HVM) to explore that user’s pursuit the final value by online group-buying.